Outcomes of surgical resection of sphenoid-orbital meningiomas with Sonopet ultrasonic aspirator. (3rd September 2021) - Ao, Jack; Juniat, Valerie; Davis, Garry; Santoreneos, Stephen; Abou-Hamden, Amal; Selva, Dinesh
ABSTRACT: Purpose : Surgical resection is the mainstay of treatment for spheno-orbital meningiomas. The Sonopet® is an ultrasonic aspirator device that provides several advantages over the traditional standard suction techniques and bone drill, including decreased collateral soft tissue damage, more precise bone removal and a clearer operative field. The purpose of the study was to examine the treatment outcomes of Sonopet®-assisted resection of spheno-orbital meningiomas. Methods : A retrospective chart review was conducted in seven patients with spheno-orbital meningioma in a single institution who underwent surgical resection with the Sonopet®. Pre-operative and post-operative data included the assessment of visual acuity, relative afferent pupillary defect (RAPD), Ishihara score, proptosis, fundus examination, computerised visual fields and the presence or absence of diplopia, headache, and other neuro-ophthalmic complications. Results : Nine Sonopet®-assisted procedures were performed on seven patients. Post-operatively, 89% of cases had stabilization or improvement of visual acuity and colour vision, whilst 29% had improved visual fields with the remainder being stable. Proptosis improved in all patients. Five of nine cases (44%) had new post-operative cranial nerve palsies, of which 75% were transient. One patient had tumour recurrence after 14 months, requiring further tumour resection and radiotherapy. Conclusion : Sonopet®-assisted resection of spheno-orbital meningiomas has comparable outcomes of visual improvement and complication rates to traditional resection techniques. Longer periods of post-operative observation and follow-up are recommended to observe long-term benefits.